Development of Genomic SSR Markers for Assessing Genetic Diversity in Korean Native Fallopia multiflora - Raveendar Sebastin; Ki Hyun Kim; Hye Ran Shin; Jin-Tae Jeong; Ju-Kyung Yu; Yoon-Sup So; Jong-Wook Chung (Horticulturae)
Fallopia multiflora, a perennial herb in the Polygonaceae family belonging to the genus Fallopia Adanson, is traditionally used as a Chinese herbal medicine. However, there is still confusion about the botanical origin of the species and the phylogenetic relationship between the cultivars and the wild relatives. To develop an efficient identification method, a molecular analysis was performed using SSR markers. The genetic diversity of the F. multiflora genetic resources has been assessed by using 10 locally collected accessions, including varieties and landraces. We screened 100 pairs of SSR primers and selected 71 successfully amplified SSR markers, in which one SSR was found to be a monomorphic marker. The results indicated that the number of alleles (NA) ranged from 2 to 10, with an average of 4.1 alleles. The major allele frequency (MAF) spanned from 0.20 to 0.90, the observed heterozygosity (HO) ranged from 0 to 0.80, and the polymorphic information content (PIC) varied between 0.16 and 0.86. Clustering analysis using an unweighted pair group mean algorithm (UPGMA) with all 70 SSR markers revealed three clusters among the F. multiflora accessions. Furthermore, seven minimum marker set combinations were identified and proved useful for variety identification. Therefore, these SSR markers could be valuable for various applications, including cultivar identification and assessing the purity of F. multiflora populations. Three genetic groups of F. multiflora should be considered as independent units for conservation and germplasm management of the species.